Embedding Local Culture in Digital Branding: A PLS-SEM Study of Teaching Factory Competitiveness in Indonesia - Ambarkahi, Ratih Puspitorini Yekti; Pratama, Fredy Eka Ardhi; Universitasari, Pascawati Savitri; Nugraheni, Ponti Primastuti Aulia (CV. SPDFHarmony, 2025)
Background: Teaching Factories (TEFAs) aim to bridge vocational learning and market demand, yet many units struggle to convert production capability into consistent market acceptance, especially in culturally laden agrifood and floriculture categories where meaning, trust, and discoverability matter. Aims: This study examines how local cultural values embedded in branding and customer perceived digitalization strengthen brand strategy coherence and, together with perceived product quality, shape market acceptance in TEFA contexts. Methods: A predictive cross sectional survey was conducted with 100 valid respondents who interacted with at least one of four TEFA units at Politeknik Negeri Jember within the last six months. Five reflective constructs were measured using seven point Likert items with three indicators per construct, local cultural values (NB), customer perceived digitalization (DG), brand strategy coherence (SB), perceived product quality (KP), and market acceptance (PS). Data were analyzed using PLS SEM with bootstrapping and predictive assessment. Result: The measurement model met reliability and validity criteria. Structural results show that NB and DG significantly increase SB, SB significantly increases PS, and KP directly increases PS. The direct DG to PS path is not significant, indicating that digitalization improves acceptance primarily through strengthening strategy coherence. Mediation tests confirm indirect effects of NB and DG on PS via SB, and predictive checks support model relevance. Conclusion: Market acceptance in TEFAs rises when cultural meaning and digital capability are organized into a coherent brand strategy and validated by reliable product quality. TEFAs can operationalize these findings by codifying place based identity assets, enforcing a simple digital playbook focused on information findability and responsiveness, and upgrading packaging to make quality cues legible at the point of choice.